Upaya Restorative Justice dalam Penanganan Kasus Tindak Pidana Korupsi - Ikhlasul Amal Imaduddin; Ali Muhammad (JOURNAL SAINS STUDENT RESEARCH, 2023)
The crime of corruption is a form of extraordinary crime which has quite serious damage to the country. The resolution of criminal acts of corruption should place more emphasis on how to restore the condition of the perpetrator so that he does not commit the same act again, then the victim, namely the state who experienced material losses, and the community who were also affected by the crime. This research uses descriptive analytical methods with a normative juridical approach. This research succeeded in finding that an emphasis on resolving crimes through a restorative approach can restore the damage and losses that occur as a result of criminal acts of corruption and prevent perpetrators from stigma and the impact of prisonization which can actually make the situation worse. Current regulations are still unable to accommodate the implementation of restorative justice effectively, so it is necessary to make improvements or create regulations that can make restorative justice efforts the main option in resolving a criminal act of corruption.